Analysis on Bridge Collapse Accidents Caused By Rainfall and Flood: A Case Study of Xiaoqing River Bridge - Hou, Yunxin (Transactions on Engineering and Technology Research, 2024)
This paper studies the structural integrity and ecological impact of Xiaoqing River Bridge in Beijing. Xiaoqing River Bridge is an important urban infrastructure spanning the Xiaoqing River, an important tributary in Beijing. Featuring a unique French design and reinforced concrete T-shape, the bridge has served a variety of urban functions for more than 40 years, including flood control and urban landscape improvement. However, the challenges posed by rapid urbanization and climate change, especially the increasing frequency and intensity of flood events, make it necessary to reassess the structural resilience and ecological impact of bridges. This paper analyzes the engineering background of the bridge, focuses on the combination of traditional and modern engineering of the bridge, and the adaptive measures taken to improve the bearing capacity and flood resistance of the bridge. The application of advanced materials and technologies in river management and ecological restoration was discussed, and the importance of environmental sustainable development and ecological balance was emphasized. The impact of climate on the bridge was studied, focusing on rainfall data for 2023 and its implications for urban planning and water management. In this paper, the collapse of river bridges caused by heavy flood is studied from the aspects of structural mechanics, historical background of material loss and bridge vulnerability. Ethical solutions to rain-induced bridge erosion are proposed, advocating responsible engineering practices, sustainable design, and robust maintenance strategies. The paper concludes with recommendations for the use of advanced technologies, such as high-resolution radar satellites, to monitor the bridge infrastructure and implement protective measures to protect the piers from erosion.